RANCANG BANGUN MESIN PENGADUK ABON LELE UNTUK KELOMPOK TANI UMKM ABON LELE - Arief, Zainal; Mundari, Siti; Yuliaty, Erma (Heuristic, 2016)
Kelompok Tani Sekar Tirta a farmer group consisting of the elderly after full duty . They chose catfish farming because it is relatively easy to handle. It turns yields less than satisfactory due to the low selling price . Hence then think about how to keep the catfish may have added value as well as the product can be long lasting. To begin try made it shredded catfish. It turns out that the results are quite as demand continues to increase . This is because the product has not been made by other manufacturers. Next made a dry pastel catfish, catfish crackers, and pia catfish. The success of these farmer groups positive impact to the surrounding community so that it can push some of the surrounding communities cultivate catfish also because demand for raw materials increases catfish .Along with the increasing demand Kelompok Tani Sekar Tirta are faced with a difficulty procuring a product , to make shredded catfish takes five hours to stir . Likewise with his catfish crackers because the thickness of the product is often found to be not as well as take a long time to cut it . Through the IbM program will fix the problem because the team managed to make IbM UNTAG Surabaya TTG mixer machine ( maker ) shredded catfish is capable of processing 20 kg of catfish in one hour . Similarly catfish chips slicing machine TTG results UNTAG IbM design team can also help slicing crackers catfish with the desired thickness is uniform and in a short time . Kata kunci: Mesin mixer dan slicer, Ikan Lele, Abon Lele